Percutaneous versus surgical strategy for tracheostomy: a systematic review and meta-analysis of perioperative and postoperative complications - Klotz, Rosa; Probst, Pascal; Deininger, Marlene; Klaiber, Ulla; Grummich, Kathrin; Diener, Markus K.; Weigand, Markus A.; Büchler, Markus W.; Knebel, Phillip (Langenbeck's archives of surgery, 2018)
PurposeTracheostomy is one of the most frequently performed procedures in intensive care medicine. The two main approaches are open surgical tracheostomy (ST) and percutaneous dilatational tracheostomy (PDT). This systematic review summarizes and analyzes the existing evidence regarding perioperative and postoperative parameters of safety.MethodsA systematic literature search was conducted in the Cochrane Library, EMBASE, LILACS, and MEDLINE to identify all randomized controlled trials (RCTs) comparing complications of ST and PDT and to define the strategy with the lower risk of potentially life-threatening events. Risk of bias was assessed using the criteria outlined in the Cochrane Handbook.ResultsTwenty-four citations comprising 1795 procedures (PDT: n = 926; ST: n = 869) were found suitable for systematic review. No significant difference in the risk of a potentially life-threatening event (risk difference (RD) 0.01, 95% CI − 0.03 to 0.05, P = 0.62, I 2 = 47%) was found between PDT and ST. There was no difference in mortality (RD − 0.00, 95% CI − 0.01 to 0.01, P = 0.88, I 2 = 0%). An increased rate of technical difficulties was shown for PDT (RD 0.04, 95% CI 0.01, 0.08, P = 0.01, I 2 = 60%). Stomal infection occurred more often with ST (RD − 0.05, 95% CI − 0.08 to − 0.02, P = 0.003, I 2 = 60%). Both techniques can be safely performed on the ICU. Meta-analysis of the duration of procedure was not possible owing to high heterogeneity (I 2 = 99%).ConclusionST and PDT are safe techniques with low incidence of complications. Both techniques can be performed successfully in an ICU setting. ST can be performed on every patient whereas PDT is restricted by several contraindications like abnormal anatomy, previous surgery, coagulopathies, or difficult airway of the patient.Systematic review registrationPROSPERO CRD42015021967